(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article analyzes the role of management and marketing strategies in the development of entrepreneurial activity. It explores the concepts of management and marketing, their main functions, and their impact on the operations of business entities. Based on statistical data, the article examines annual trends in the number of enterprises and organizations operating in the Republic of Uzbekistan, as well as the management and marketing factors influencing their development. Recommendations are provided on enhancing competitiveness, identifying customer needs, and developing effective strategies. The study outlines ways for entrepreneurial entities to achieve sustainable growth by integrating management and marketing strategies.